Canning Processes Reduce the DNA-Based Traceability of Commercial Tropical Tunas - Carlo Pecoraro; Valentina Crobe; Alice Ferrari; Federica Piattoni; Anna Sandionigi; Adam J. Andrews; Alessia Cariani; Fausto Tinti (Foods, 2020)
Canned tuna is one of the most widely traded seafood products internationally and is of growing demand. There is an increasing concern over the vulnerability of canned tuna supply chains to species mislabelling and fraud. Extensive processing conditions in canning operations can lead to the degradation and fragmentation of DNA, complicating product traceability. We here employed a forensically validated DNA barcoding tool (cytochrome b partial sequences) to assess the effects of canning processes on DNA degradation and the identification of four tropical tuna species (yellowfin, bigeye, skipjack and longtail tuna) collected on a global scale, along their commercial chains. Each species was studied under five different canning processes i.e., freezing, defrosting, cooking, and canning in oil and brine, in order to investigate how these affect DNA-based species identification and traceability. The highest percentage of nucleotide substitutions were observed after brine-canning operations and were greatest for yellowfin and skipjack tuna. Overall, we found that DNA degradation significantly increased along the tuna canning process for most specimens. Consequently, most of the specimens canned in oil or brine were misidentified due to the high rate of nucleotide substitution in diagnostic sequences.